1990
DOI: 10.2307/1937604
|View full text |Cite
|
Sign up to set email alerts
|

Competition, Fire, and Nutients in a Mixed‐Grass Prairie

Abstract: Variation in the intensity of competition has been proposed as a mechanism that may control the species diversity and composition of many kinds of communities, including North American prairie. Competition intensity is predicted to increase with soil fertility and decrease with disturbance, causing variation in the abundances of competitively subordinate species. Variation in competition intensity was examined in an experiment in which fire and fertilizer were applied to native mixed—grass prairie. Treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
78
4
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 35 publications
9
78
4
1
Order By: Relevance
“…Wilson and Keddy 1986;Campbell and Grime 1992;Turkington et al 1993;Bonser and Reader 1995;Gaudet and Keddy 1995;Kadmon 1995) or to have no relation to productivity (e.g. Welden et al 1988;Di Tomasso and Aarssen 1991;Wilson and Shay 1990;Wilson and Tilman 1993;Cahill 1999). Our results show a clear relationship between community above-ground phytomass and competition intensity when the latter is calculated using population-level measures, such as number of shoots.…”
Section: Resultscontrasting
confidence: 44%
“…Wilson and Keddy 1986;Campbell and Grime 1992;Turkington et al 1993;Bonser and Reader 1995;Gaudet and Keddy 1995;Kadmon 1995) or to have no relation to productivity (e.g. Welden et al 1988;Di Tomasso and Aarssen 1991;Wilson and Shay 1990;Wilson and Tilman 1993;Cahill 1999). Our results show a clear relationship between community above-ground phytomass and competition intensity when the latter is calculated using population-level measures, such as number of shoots.…”
Section: Resultscontrasting
confidence: 44%
“…The direction, magnitude, and depth of influence of these changes in the soil depends on myriad factors including maximum burn temperature, length of burn, fuel composition, soil texture, and water content (Wright and Bailey, 1982). The changed nutrient status of the soil, as well as, heat-induced production of germination cues, release of competition, production of phytotoxic substances, and destruction of germination inhibitors, all influence post-fire natural plant recruitment dynamics and post-wildfire community structure (Christensen and Muller, 1975;Keeley et al, 1985;Sonneveld and Voogt, 1973;Went et al, 1952;Wilson and Shay, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…These changes in morphology will likely translate into increased biomass and seed count during successive seasons due to increased light capture ability (Schmitt and Dudley 1996). Similarly, Wilson and Shay (1990) found that basal circumference increased in perennial grasses when neighbors were removed in a Canadian mixed-grass prairie. L. multiflorum, the only non-perennial, was able to capitalize on the reduction in competition to produce more aboveground biomass, which was highly correlated (r = 0.92) with seed production.…”
Section: Discussionmentioning
confidence: 92%